The Influence of Leader Behavior and Employee Empowerment on Employee Performance Mediated by Work Motivation on Employees of the Aru Islands Regency Transportation Service - Kailuhu, Wilhelmina; Lewaherilla, Novalien C.; Leuhery, Ferdy (Jurnal Ekonomi, 2024)
This study aims to determine the effect of leader behavior and employee empowerment on employee performance mediated by work motivation. Sampling in this study used a sample of 56 respondents. The data collection method used was interviews and questionnaires. The analysis method used is Partial Least Square - Structural Equation Modeling (PLSSEM). The variables analyzed in this study are Leader Behavior, Employee Empowerment, Employee Performance and Work Motivation. The results of the study indicate that there are variables that have a significant effect, namely. Leader behavior has a positive and significant effect on Employee performance, performance empowerment has a significant effect on Employee Performance, leader behavior has a significant effect on Work Motivation, employee empowerment has a significant effect on Work Motivation, Work Motivation has an effect on employee performance, leader behavior has a significant effect on employee performance mediated by Work Motivation, employee empowerment has a significant effect on Employee performance, which is mediated by Work Motivation.